Self-Efficacy In Entrepreneurship As A Mediator Between Industrial Work Practice And Entrepreneurship Education - Haqi, Syafrozi; Puji Handayati; Agus Hermawan (International Journal of Business and Quality Research, 2025)
This research holds high urgency given the high rate of educated unemployment in Indonesia, particularly among Vocational High School (SMK) graduates. The study's core focus is analyzing the crucial role of vocational education in creating graduates who are not only job-ready but also capable of entrepreneurship. Using a quantitative, cross-sectional design on 12th-grade Marketing students at State Vocational High Schools in Mojokerto Regency, the study specifically aims to test the influence of Industrial Work Practice (Prakerin) and Entrepreneurship Education on Entrepreneurial Motivation, with Self-Efficacy as a mediating variable. Data analysis will be conducted using Partial Least Square-Structural Equation Modeling (PLS-SEM). While the final results are not yet available, the research is expected to reveal that Self-Efficacy acts as a significant mediator. This implies that the Prakerin experience and entrepreneurship coursework must first successfully foster students' self-confidence before their entrepreneurial motivation can be adequately boosted. Based on this framework, the key recommendations are to optimize the quality and duration of Prakerin and to reform Entrepreneurship Education methods to focus more on developing Self-Efficacy through intensive business simulations and real-world projects. Ultimately, these findings are expected to provide vital insights into how industrial experience and formal education can be better aligned to effectively encourage entrepreneurial aspirations among SMK graduates